2021
DOI: 10.1038/s42003-021-02164-4
|View full text |Cite
|
Sign up to set email alerts
|

A single resistance factor to solve vineyard degeneration due to grapevine fanleaf virus

Abstract: Grapevine fanleaf disease, caused by grapevine fanleaf virus (GFLV), transmitted by the soil-borne nematode Xiphinema index, provokes severe symptoms and economic losses, threatening vineyards worldwide. As no effective solution exists so far to control grapevine fanleaf disease in an environmentally friendly way, we investigated the presence of resistance to GFLV in grapevine genetic resources. We discovered that the Riesling variety displays resistance to GFLV, although it is susceptible to X. index. This re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recessive factor of resistance against GFLV was recently described in V. vinifera cv. Riesling, providing interesting perspectives for fanleaf management [ 33 ]. However, at least two decades of research will be needed for characterizing this resistance factor, its sustainability, and introducing this genetic trait in grapevine genotypes prior to the deployment of new resistant hybrids in vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…A recessive factor of resistance against GFLV was recently described in V. vinifera cv. Riesling, providing interesting perspectives for fanleaf management [ 33 ]. However, at least two decades of research will be needed for characterizing this resistance factor, its sustainability, and introducing this genetic trait in grapevine genotypes prior to the deployment of new resistant hybrids in vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…This is because when working with X. index we have found that nematodes survive and reproduce better using the former method, presumably because they are not subject to the stress of the extraction, storage and dilution steps preceding inoculation; we therefore hypothesised that this is also the case for X. diversicaudatum. This protocol is also used to evaluate the transmission efficiency of GFLV variants (Marmonier et al, 2010;Schellenberger et al, 2010;Andret-Link et al, 2017) or to evaluate plant resistance to GFLV infection (Hemmer et al, 2018;Djennane et al, 2021). Interestingly, with this inoculation method, our results have provided the first data illustrating different host suitabilities to X. diversicaudatum amongst grapevine accessions.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, its limited tolerance to phylloxera (Daktulosphaira vitifoliae) and a broad spectrum of nematodes, including root-knot nematodes (Meloidogyne incognita, M. arenaria, M. hapla, and M. javanica), as well as dagger nematode caused by Xiphinema index, has emerged as primary concerns within the feld of viticulture as previously reviewed by other researchers [28]. Furthermore, the majority of V. vinifera varieties are susceptible to infection by grapevine fanleaf virus, a soilborne Nepovirus transmitted by the dagger nematode (X. index) that could cause fanleaf disease [34].…”
Section: Main Parent Species For Rootstock Breeding and Existing Type...mentioning
confidence: 99%